2020
DOI: 10.14744/tjtes.2020.25260
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of plasma and tissue fibronectin EIIIB splice variant expressions measured serially with RT-PCR in a wound model of rabbits

Abstract: BACKGROUND: Fibronectin (FN) is an indispensable part of the extracellular matrix. During regeneration or wound healing, the plasma form of FN is incorporated into the fibrin clots to form a temporary fibrin-FN matrix, and also locally synthesized cellular FN migrates to the clot to regenerate the injured tissue. We aimed to examine wound tissue FN EIIIB and plasma FN EIIIB expression levels in an experimental wound healing model in rabbits. METHODS:Plasma and tissue EIIIB splice variant expressions were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Fibroblasts and many growth factors released from them increase during the healing process and contribute to wound healing. It has also been reported that PRP application increases fibroblast migration and proliferation 28,29 . This study detected a significantly reduced fibrosis score histopathologically in the PRP group compared to the control group.…”
Section: Macroscopic Adhesion Control Group Prp Groupmentioning
confidence: 89%
“…Fibroblasts and many growth factors released from them increase during the healing process and contribute to wound healing. It has also been reported that PRP application increases fibroblast migration and proliferation 28,29 . This study detected a significantly reduced fibrosis score histopathologically in the PRP group compared to the control group.…”
Section: Macroscopic Adhesion Control Group Prp Groupmentioning
confidence: 89%